New media and the rise of the popular woman writer, 1832-1860 - Easley, Alexis, 1963- (Edinburgh critical studies in Victorian culture., 2021)
This book highlights the integral relationship between the rise of the popular woman writer and the expansion and diversification of newspaper, book and periodical print media during a period of revolutionary change, 1832-1860.